Scoping review to assess the reach, effectiveness, and impact of government-funded, population-based physical activity initiatives in Australian adults - Dissanayaka Mudiyanselage, C. H. B.; Chappel, Stephanie E.; Irwin, Sidney; Fisher, Gabrielle; Crozier, Alyson J.; Vandelanotte, Corneel (Frontiers in Sports and Active Living, 2025)
IntroductionIn Australia, physical activity initiatives are often implemented by state and federal governments to enhance population-wide physical activity levels. Given the complexity and variability of government-funded physical activity programs, a scoping review is needed to synthesise the existing evidence and identify gaps in current initiatives. The aim of this review is to explore the reach, effectiveness, and impact of government-funded, population-based physical activity initiatives targeting Australian adults.MethodsThis scoping review was conducted in accordance with the PRISMA extension for Scoping Reviews (PRISMA-ScR). PubMed, Scopus, Web of Science, MEDLINE, and ProQuest Public Health were searched for articles published between January 2000 and April 2024. Search terms included relevant terms surrounding the main topics of “physical activity,” “intervention,” “population-based,” “government-funded,” and “Australia.” Grey literature was collected from the websites of relevant organisations, health agencies of Australian states and territories, and other government departments. In addition, a manual search of references listed in primary sources was conducted to find journal articles missed during the database search. A narrative synthesis of included studies was conducted.ResultsIn total, 6,127 sources were identified, of which 71 were included in the final review. The peer-reviewed studies and grey literature evaluation reports identified physical activity initiatives across all Australian states and at the national level. Queensland and Victoria reported a greater number of physical activity interventions, strategies, and action plans compared to other states. The most common intervention strategies involved the use of digital platforms and a combination of multiple strategies.DiscussionWhile most of these initiatives increased physical activity, their overall reach to the broader Australian population was limited. The initiatives positively impacted individuals’ health (e.g., weight, mitigating chronic diseases) and well-being (e.g., developing social connections). Although these initiatives have demonstrated improvements in physical activity and community health and well-being, they have only reached a small fraction of the Australian population. This review highlights the need for a National Physical Activity Plan. While many states have published high-quality strategies and action plans, there is a pressing need for their actual implementation to assess effectiveness. Future research should focus on standardising evaluation frameworks and exploring strategies to enhance the sustainability and effectiveness of initiatives, particularly in diverse populations.Systematic Review Registrationhttps://osf.io/6aev4/registrations, identifier 6aev4.